PEMBERIAN DISPENSASI KAWIN ANAK DIBAWAH UMUR MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 1974 - Fajar; Muriani (Fakultas Hukum Universitas Trisakti, 2022)
Age restriction is a crucial prerequisite for marriage. An application for marital dispensation can be made to the court, and the court will grant a dispensation from marriage if the minimum age requirement has not been satisfied. The problem is formulated as follows: Are the legal ramifications of granting a marriage dispensation in decision number 0080/Pdt.P/2020/PA.Dpk by the Depok court consistent with Law Number 1 of 1974 and Law Number 16 of 2019? The type of study being done by normative legal, analytical descriptive in character, and deductive logic is employed to draw conclusions after processing qualitative data and utilising secondary data. Research findings, a discussion, and a conclusion the legal implications of granting the marital dispensation is giving rise to rights and obligations among the applicant as husband and wife, and also the applicant's dispensation can enter into marriage, are inconsistent with the decision Number 0080/Pdt.P/2020/PA.Dpk with the relevant law regarding the marital dispensation granted by PA Depok. In order to decrease the incidence of early marriages, the panel of judges gave closer consideration to the justifications for requesting a marriage dispensation.